Trends in number theory : Fifth Spanish Meeting on Number Theory, July 8-12, 2013, Universidad de Sevilla, Sevilla, Spain - Jornadas de Teoría de Números; Chamizo, Fernando; Guàrdia, Jordi; Rojas León, Antonio; Tornero, José María (Contemporary mathematics, 2015)
This volume contains the proceedings of the Fifth Spanish Meeting on Number Theory, held from July 8-12, 2013, at the Universidad de Sevilla, Sevilla, Spain.The articles contained in this book give a panoramic vision of the current research in number theory, both in Spain and abroad. Some of the topics covered in this volume are classical algebraic number theory, arithmetic geometry, and analytic number theory.This book is published in cooperation with Real Sociedad Matematica Espanola (RSME).